Evaluasi Program Pengelolaan Sampah Hasil Rumah Tangga - Rohmah Nur Rosanti, Vita Dwi; Pasca Budiono, Nugrahadi Dwi (IAI Nasional Laa Roiba Bogor, 2024)
The problem of household waste is the responsibility of all parties, including the village government and the community itself. In the implementation of the waste management program in Kemantren Village it has not been effective and efficient so an evaluation of this program is needed. This research aims to evaluate the household waste management program in Kemantren Village, Tulangan District, Sidoarjo Regency. The type of research is descriptive qualitative by collecting data using observation and interview techniques. This research uses a program suitability model by David Korten. The results of the research show that the problem of household waste in Kemantren Village has not been resolved optimally, so a household waste management program has been implemented since 2018 by the village government. This waste management program includes collecting and transporting waste using three-wheeled trucks and operational costs come from mandatory monthly fees. based on the program suitability model by David Korten that the household waste management program in Kemantren village is not running effectively and efficiently because there is a mismatch between the elements of the waste management program and the capacity of human resources in implementing this waste management program.